Business, ethics and peace - Bouckaert, Luk, 1941-; Chatterji, Manas, 1937- (Bingley, U.K. : Emerald, 2015)
Good business needs a peaceful and just world in which to operate and prosper. Likewise, peace thrives in a healthy economic environment. However, many companies - either directly or indirectly - are involved in the arms race and in a battle to exploit and control scarce resources. As a result of the ambiguous power of business, a timely reflection on its impact on war and peace is needed as well as a conscious pro-peace commitment. Business, Ethics and Peace gathers a selection of papers presented at the International SPES Conference Business for Peace, Strategies for Hope at Ypres, April 10-12, 2014. Among the many initiatives commemorating the centennial of World War I, this project focuses on the ethical need to prevent the next conflict. It interprets and presents peace as a holistic and evolving concept, defining the need for an ethical charter of human rights and responsibilities. The papers illustrate the impact of religion in peace management and present solutions and practices for corporate peace-building.
The evolving view on peace and its implications for business / Linda Groff, Luk Boukaert -- Peace in an organic worldview / Knut J. Ims, Ove D. Jakobsen -- The passion and imagination for peace / Walter G. Moss -- The wisdom of mercy as the foundation of business and peace : the alternative to fear / Hendrik Opdebeeck -- A culture of peace : common ground for joint action / Edy Korthals Altes -- Responsibility is the way : clouds and silver linings around the idea of 'business for peace' / Edith Sizoo -- Human rights and individual responsibility : identifying the individual 'margin of appreciation' / Michae<U+0308>l Merrigan --Co-charismatic leadership and peacebuilding : inspiration from John Paul Lederach / Simon Robinson, Jonathan Smith -- A path to a peaceful world for the common good / Kamran Mofid -- The concept of 'peace management' from a Sikh-Indian perspective / Gerrit De Vylder -- Islam and peace / Jonas Yunus Atlas -- Leadership in peacemaking : a Christian view / Elfrida Calvocoressi -- Business for world peace : a Baha'i perspective / Daniel Truran -- Ecology for peace : the Franciscan legacy / Thomas Dienberg -- The spirit of non-violence and peace in business / Ga<U+0301>bor Kova<U+0301>cs, Andra<U+0301>s O<U+0301>csai -- Putting a price on peace : the total cost of violence to the global economy / Thomas Morgan -- Ethical reasoning in global decision-making / Steven Scalet, Thomas F. Kelly -- Peace-entrepreneurs : the peacestartup experience in Colombia / Maria Prandi -- Without memory there would be no Conflict? The role of memory in organizations in a system theoretical approach / Lisette Peulen -- Mediation and negotiation in business conflicts / Piet Vandeputte -- 'Buurtzorg' : a case of being-centredness as example of an organic worldview for corporate peace / Sharda Nandram -- Sustainable fashion and animal welfare : non-violence as a business strategy / Ingrid Molderez, Perrine De Landtsheer.
Includes index.
Print version record
Keywords: Political Science -- Peace; Peace studies & conflict resolution; Business ethics; Peace